OP0183 Jadas Remission and Minimal Disease Activity upon First Biologic in Jia. (10th June 2014) - Horneff, G.; Von Stackelberg, S.; Foeldvari, I.; Haas, J.P.; Ganser, G.; Minden, K.; Hospach, A.
Abstract : Background: Remission and minimal disease activity have been proposed as treatment goal as both can be achieved. For both JADAS based definitions have been proposed. Methods: This retrospective analysis used data of the German BIKER-registry the course of JADAS10 (Physician global assessment VAS 0–10-cm, Parent/patient global assessment VAS 0–10-cm, Active joint count 0-71, truncated at 10, normalized ESR [ESR-20/10], range 0-40) upon first biologic regimen. A JADAS<1 was used to define remission, JADAS<3.8/<2 were used as cut-off to define minimal disease activity in polyarticular course/oligoarthritis pts. Results: 2111 JIA pts starting a first biologic were identified. 1830 received Etanercept (ETA), 209 Adalimumab (ADA) and 33 Tocilizumab (TCZ). Biologics not approved for first line therapy (Abatacept, Anakinra, Infliximab, Golimumab) were used in of 39 pts only. Therefore analysis of the latter patient cohorts seemed not reasonable. Baseline parameters differed for the chosen drugs group. Patients receiving ADA first more often have had chronic uveitis and were more often ANA positive. Age at onset, disease duration, distribution of JIA categories and pretreatments were comparable between ETA and ADA, while TCZ was used more frequently in systemic JIA (table 1). Disease activity indicators at baseline were highest in the ETA group followed by TCZ and lowest with ADA. ESR& CRP were highest in TCZ starters. Upon treatment, the median JADAS decreased in all JIA categories. After 12 months on treatment with ETA, depending of the JIA categories, 28% to 42% of pts had a JADAS<1 defining remission, minimal disease activity (JADAS<3.8) was reached by 50-69% of polyarticular JIA pts and 69% in oligoarticular JIA (JADAS<2). The rates further increased over the treatment time. Similar rates for remission and low disease activity were reached with ADA. Because mostly systemic JIA patients were recruited in the TCZ cohort, results were not directly comparable. Conclusions: ETA is by far the most frequently used biologic in JIA pts. ADA is preferred in pts with a history of uveitis, while TCZ is preferred in systemic JIA. Minimal disease activity is reached by the majority of pts but remission only by a part. In summary, a treat to target approach seems reasonable in JIA patients. New therapeutic options are needed for JIA patients with refractory disease. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.2336